Cigarette smoking and male lung cancer in an area of very high incidence. I. Report of a case-control study in the West of Scotland. Issue 1 (March 1988) - Gillis, C R; Hole, D J; Boyle, P
Abstract : Altogether 656 male lung cancer cases and 1312 age and sex matched controls were interviewed between 1976 and 1981 in a case-control study of cigarette smoking habits and lung cancer in Glasgow and the West of Scotland, an area with the highest recorded incidence in the world. The relative risk of lung cancer increased significantly for smokers whose consumption was below 20 cigarettes per day but did not rise significantly in those who smoked more than 20 cigarettes per day. Other smoking characteristics such as inhalation and tar yields of brands smoked did not explain this finding. Additionally, the relative risks observed at all levels of cigarette consumption were low in comparison with those in the published literature. By constructing an index of cigarette exposure which included the tar yields of brands smoked, an assessment of the risk of lung cancer in relation to tar exposure independent of amount smoked was derived. Only in smokers of less than 15 cigarettes per day was there a statistically significant reduction in risk of lung cancer associated with lower levels of tar yield.